Transplant Outcomes in Patients with Idiopathic Membranous Nephropathy - Claire Kennedy; Carol Traynor; Patrick O'Kelly; Anthony Dorman; Peter J. Conlon (International Journal of Nephrology)
Background. The natural history of idiopathic membranous nephropathy and recurrent disease in transplants is variable. We performed a retrospective cohort study of renal transplant recipients with a primary diagnosis of idiopathic membranous nephropathy. We aimed to establish patterns of disease recurrence and to identify factors associated with disease recurrence. Methods. We accessed the Irish renal transplant database to identify patients with biopsy-proven idiopathic membranous nephropathy in receipt of a renal transplant between 1982 and 2010. A detailed medical chart review was performed in all cases, and a senior renal histopathologist reviewed all histology specimens. Results. The outcomes of 32 patients, in receipt of 36 grafts, are reported. There was a male preponderance (). Significant graft dysfunction, directly attributable to recurrent disease, was evident in 31% of cases at 10 years. There was no significant association between time on dialysis, HLA mismatch, occurrence of rejection, and the development of recurrent membranous disease. One patient was retransplanted twice; all three grafts were lost to aggressive recurrent membranous disease. Conclusions. It remains difficult to identify those that will develop recurrent membranous nephropathy. Almost one third of patients in this cohort developed clinically significant recurrent disease at 10 years.